Differential geometry of intersection curves in R(4) of three implicit surfaces - Alessio, Osmar [UNESP] (Elsevier B.V., 2009)
We present algorithms for computing the differential geometry properties of intersection Curves of three implicit surfaces in R(4), using the implicit function theorem and generalizing the method of X. Ye and T. Maekawa for 4-dimension. We derive t, n, b(1), b(2) vectors and curvatures (k(1), k(2), k(3)) for transversal intersections of the intersection problem. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Implicit-implicit-implicit intersection; Surface-surface-surface intersection; Transversal intersection; Geometric properties; Implicit curves